IMPROVING THE COOPERATION OF PRESCHOOL AND PRIMARY EDUCATION PEDAGOGUES IN THE PROCESS OF INCLUSIVE EDUCATION - Juraboyeva Mastura; Jalolova.M (TADQIQOTLAR, 2025)
Annotation: This work focuses on improving the cooperation between preschool and primary education pedagogues within the framework of inclusive education. The study emphasizes the importance of continuity in pedagogical approaches, mutual understanding of developmental needs, and coordinated support strategies for children with special educational needs. It explores methods of fostering professional collaboration, joint planning, and communication between educators to ensure a smooth transition and consistent support for learners. The outcomes aim to contribute to more effective inclusive practices and a unified educational environment.